Le gore : du cinéma à la littérature - Gadomska, Katarzyna (Romanica Silesiana)
The gore is a modern supernatural where the blood is the most important element. This phenomenon of the pop culture is born in the cinema with wave of the slasher movies and, later, he’s coming in the literature of supernatural, named also the mainstream horror. The constituent elements of the gore there are: — the mad serial killer in the mask, — the space of a giant city, — the blood and the terror, — the extreme cruelty (the murders, the tortures etc.). The present study is analysing of these elements in the movies and the French short stories gore. Key words: Gore, mainstream horror, blood, mad serial killer, modern supernatural, urban legends, terror, slasher movie.